Synthesis of highly crystalline multilayered Boron niride microflakes - Ahmad, P.; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Muhammad, N. (Nature Publishing Group, 2016)
Boron niride microflakes of 2-5 μm in diameter and greater than 40 μm in length with multilayer structure and highly crystalline nature are synthesized in two states of catalysts and dual role of nitrogen at 1100 °C. Most of the microflakes are flat, smooth and vertically aligned with a wall-like view from the top. Transmission electron microscopy shows overlapped layers of microflakes with an interlayer spacing of 0.34 nm. The h-BN components of the synthesized microflakes are verified from B 1s and N1 s peaks at 190. 7 and 397.9 eV. Raman shift at 1370 (cm-1) and sharp peaks in the XRD pattern further confirm the h-BN phase and crystalline nature of the synthesized microflakes. Microflakes of h-BN with the above characteristics are highly desirable for the development of a solid state neutron detector with higher detection efficiency.